Enzyme activity and trophic links of macroarthropods living on an exposed Mediterranean beach–dune system. Issue 2 (2nd April 2016) - Lagar, M. C.; Pazzagli, L.; Cappugi, G.; Giusfredi, G.; Colombini, I.; Fallaci, M.; Chelazzi, L.; Scapini, F.
Abstract: Arthropod communities of beach–dune systems are mainly composed by detritivorous species, apparently with overlapping trophic niches. This study aims at distinguishing the trophic roles of sympatric species, by using a biochemical approach in the analysis of gut contents. The digestion of seven trisaccharidic and disaccharidic substrates containing the glycosidic bond was tested in gut homogenates of 10 species of detritivorous insects and crustaceans from a Mediterranean beach–dune system (Tuscany, Italy). Glycosidase activities were compared between species. A dendrogram was determined separating species with different enzymatic activity spectra. The differences observed in the enzymatic activities may be related to a different use of the available food resources and interpreted as an opportunist nutrition of arthropod species sharing the same habitat.